Adaptive Physiological and Morphological Adjustments Mediated by Intestinal Stem Cells in Response to Food Availability in Mice - Peña-Villalobos, Isaac; Casanova-Maldonado, Ignacio; Lois, Pablo; Sabat, Pablo; Palma, Verónica (Frontiers in Physiology, 2019)
Several studies have evaluated plastic changes in the morphology of the digestive tract in rodents subjected to caloric restriction or restricted availability. Nevertheless, studies that link these morphological responses to physiological consequences are scarce. In order to investigate short-term plastic responses in the intestine, we acclimated adult Mus musculus (BALB/c) males for twenty days to four distinctive treatments: two caloric regimens (ad libitum and 60% of calorie ingestion) and two levels of periodicity of the regimens (continuous and stochastic treatment). At the end of the treatment we analyzed the cell proliferation and cell death dynamics of small intestinal crypts in these animals. In addition, we measured organ masses and lengths, hydrolytic digestive enzymes activities and energy output from feces. Finally, in order to explore the metabolic changes generated by these dietary conditions we assessed the catabolic activity (i.e., enzymes) of the liver. Our results show that individuals acclimated to a continuous and 60% regimen presented longer intestines in comparison to the other treatments. Indeed, their intestines grew with a rate of 0.22 cm/day, generating a significant caloric reduction in the content of their feces. Besides, both mass and intestinal lengths were predicted strongly by the stabilization coefficient of BrdU+ proliferating cells per crypt, the latter correlating positively with the activity of n-aminopeptidases. Interestingly, by using pharmacological inhibition of the kinase Mammalian target of rapamycin (mTORC1) by Rapamycin, we were able to recapitulate similar changes in the proliferation dynamics of intestinal stem cells. Based on our results, we propose that the impact of caloric restriction on macroscopic variation in morphology and functional changes in digestive n-aminopeptidases occurs through synchronization in the proliferation rate of stem and/or progenitor cells located in the small intestinal crypts and requires mTORC1 as a key mediator. Hence, we suggest that an excessive stem and progenitor activity could result in increased crypts branching and might therefore underlie the reported intestinal tissue expansion in response to short-term caloric restriction. Summarizing, we demonstrate for the first time that short-term caloric restriction induces changes in the level of cell proliferation dynamics explaining in part digestive tract plasticity in adaptive performance.